Hb Phnom Penh: clinical characteristics analysis and literature review - Jian-lian Liang; Yi-yuan Ge; Jing-wei Situ; Jin-xiu Yao; Jin-ling Chen; Long-xu Xie; Li-ye Yang (Hematology)
Objective To summarize and analyze the clinical characteristics of the Hb Phnom Penh (HBA1:c.354_355insATC) variant in the Chinese population, and to guide clinical diagnosis and genetic counseling for hemoglobin disorders.Methods Peripheral blood samples were collected from patients, and hematological parameters, hemoglobin electrophoresis, and glycated hemoglobin chromatography were analyzed. PCR combined with reverse dot blot hybridization (RDB), nested PCR, gap polymerase chain reaction (Gap-PCR), Sanger sequencing, and third-generation sequencing (TGS) were performed to determine the gene variant.Results A total of 20 cases were examined, which included 11 neonates, 5 infants aged from 1 month to 6 months, and 4 adults. Hb Bart’s band was measured in 14 infants. Thirteen infants (9 neonates and 4 infants of 1 month old) showed low levels of Hb Bart’s bands (<1%), while one newborn exhibited a significantly elevated level of the Hb Bart’s band (13.8%). Two adult patients were tested for glycated hemoglobin and had high levels at 7.0% and 7.2%, respectively, despite having normal blood glucose levels and no history of diabetes, indicating the presence of abnormal hemoglobin. Genetic testing confirmed that all 20 cases carried the HBA1:c.354_355insATC mutation, with one case being a compound mutation of – SEA/ααPhnom Penh.Conclusion The HBA1:c.354_355insATC mutation leads to the production of abnormal hemoglobin (Hb Phnom Penh). Infants may exhibit low levels of Hb Bart’s bands on hemoglobin electrophoresis, which have no salient pathological significance. The detection of abnormal HbA1c values suggests that this abnormal haemoglobin may be present.